Structural and morphological characteristics of (Pb1-x Sr (x) )TiO3 powders obtained by polymeric precursor method - Leal, S. H.; Sczancoski, J. C. [UNESP]; Cavalcante, L. S. [UNESP]; Escote, M. T.; Matos, J. M. E.; Santos, M. R. M. C.; Pontes, Fenelon Martinho Lima [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Springer, 2010)
Pb1-x Sr (x) )TiO3 powders with different compositions (x = 0, 0.10, 0.50, 0.90 and 1) were synthesized by the polymeric precursor method and heat treated at 800 A degrees C for 2 h under air atmosphere. The thermogravimetric and differential scanning calorimetry analyses were performed in the range from 25 to 800 A degrees C in order to estimate the stages corresponding to the water evaporation, organic decomposition and crystallization of these materials. X-ray diffraction patterns and Rietveld analyses showed that the (Pb1-x Sr (x) )TiO3 phases with strontium content up to x = 0.1 crystallize in a tetragonal structure. The micrographs obtained by scanning electron microscopy and transmission electron microscopy showed that the powders have agglomerated nature, presenting irregular morphologies and polydisperse particle size distribution. The energy dispersive X-ray spectrometry indicated the presence of pure (Pb0.50Sr0.50)TiO3 phase.
Keywords: (Pb1-xSrx)TiO3; Inorganic materials; Chemical synthesis; Nanosized powder